Analisis Miskonsepsi Peserta Didik pada Materi Struktur Atom Menggunakan Five-Tier Multiple Choice Diagnostic Test Berbasis Piktorial - Nufus, Sururin; Silfianah, Ifah (Chemistry Education Department of Education and Teaching Faculty, 2023)
Misconceptions are one of the causes of students learning difficulties. One of the misconceptions about chemistry is the atomic structure. In general, chemistry subjects are abstract and difficult to visualize. It causes students to find it difficult to understand chemical concepts correctly. Misconceptions that occur in students will have an impact on understanding further material. Therefore, it is necessary to do an analysis to identify students who experience misconceptions so that efforts can be made to prevent and correct them. Misconceptions experienced by students can be identified through diagnostic tests, one of which is the five-tier diagnostic test. Most of the five-tier diagnostic tests used are narrative-based, which triggers student saturation. Therefore, this study uses a five-tier diagnostic test combined with a pictorial test. This research is to find out students misconceptions experienced by X-class SMA in the matter of atomic structure. This study uses a quantitative descriptive method. The instrument used in this study was a pictorial-based, five-tier diagnostic test consisting of 24 items. The results showed that students experienced misconceptions about atomic structure material with an average percentage of 20%. Students experience misconceptions about the concept of the development of atomic theory (18%), atomic constituent particles (23%), isotones, isobars, and isotopes (21%), and electron configurations (20%). Factors that cause misconceptions experienced by students include their prior knowledge, their interest in studying atomic structure material, the sources of their personal thoughts, their low ability and reasoning in understanding atomic structure material, and their lack of instilling concepts in them.